Corrigendum to "Laboratory investigations of the impact of mineral dust aerosol on cold cloud formation" published in Atmos. Chem. Phys., 10, 11955–11968, 2010 - K. A. Koehler; S. M. Kreidenweis; P. J. DeMott; M. D. Petters; A. J. Prenni; O. Möhler (Atmospheric Chemistry and Physics, 2011)
No abstract available.